THE EFECTIVENESS OF PROVIDING OREM SELF CARE BASED HEALTH EDUCATION ON IMPROVING THE QUALITY OF LIFE OF BREAST CANCER PATIENTS - Kristina, Kristina; Noer Saudah; Lilik Ma'rifatul Azizah; Indah Lestari; Reni Anggraeni Dwi (Universitas Airlangga, 2024)
Introduction: Breast cancer can cause many problems, both psychosocial and physical problems, which can reduce the patient's quality of life. Therefore, an intervention is needed that can improve their quality of life. This study aims to analyze the benefits of the intervention of implementing a self-care orem-based education system to improve the quality of life of breast cancer chemotherapy patients at Graha Amerta Surabaya. Method: This study used a pre-experimental design with a one-group pre-posttest design method on 60 breast cancer patients treated with chemotherapy who were taken using a consecutive sampling technique. The quality of life instrument was measured using the EORTC QLQ-C30 questionnaire. Data were analyzed using the Wilcoxon signed rank statistical test. Results: The results of the study showed that after being given the intervention to implement an educational system based on self-care orem, the results showed that the majority of 39 (65.0%) respondents had a quality of life in the good category and 21 (35.0%) respondents had a quality of life in the sufficient category. The results of the Wilcoxon statistical test analysis on the quality of life of breast cancer patients produced a significance value of 0.000. Conclusion: There is a significant effect of implementing an OREM self-care system education on improving the quality of life of breast cancer chemotherapy patients at Graha Amerta Surabaya. It is hoped that nurses can implement interventions to implement educational systems based on self-care orem for breast cancer patients in hospitals so that patient independence can increase so that the patient's quality of life can be optimal.